Gilles Deleuze - Colebrook, Claire (Routledge, 2002)
Why think? Not, according to Gilles Deleuze, in order to be clever, but because thinking transforms life. Why read literature? Not for pure entertainment, Deleuze tells us, but because literature can recreate the boundaries of life. With his emphasis on creation, the future and the enhancement of life, along with his crusade against 'common sense', Deleuze offers some of the most liberating, exhilarating ideas in twentieth-century thought. This book offers a way in to Deleuzean thought through such topics as: * 'becoming' * time and the flow of life * the ethics of thinking * 'major' and 'minor' literature * difference and repetition * desire, the image and ideology. Written with literature students in mind, this is the ideal guide for students wishing to think differently about life and literature and in this way to create their own new readings of literary texts.